Economic impact studies and methodological bias : the case of the National Arts Festival in South Africa - Bragge, Brent Reuben (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
Over the course of the last three decades, it has become popular practice to evaluate tourism events like cultural festivals in financial terms, through the use of economic impact studies. This can be attributed at least in part to the notable growth in the number of festivals being held globally and, as such, a higher level of competition between festivals for the limited funding which is available. Economic impact studies, and the resultant findings, have thus become powerful tools for the lobbying of sponsorship, and it has become increasingly important that the impact calculations be as accurate as possible, so as to effectively allocate both government and private resources to projects which will be of the greatest benefit to the host region. The allocation of funding is especially vital in an area like the Eastern Cape Province of South Africa, which is faced with many financial difficulties. The allocation of public funds to an event like the National Arts Festival, which is hosted in a relatively wealthy part of the province, might be weighed against initiatives which directly benefit the poorer parts of the region. Although it is acknowledged that the benefits which are felt by the host community of a cultural event go beyond that of the financial, it is often on this basis that festivals are most easily compared. The primary goal of the thesis was to analyse the various forms of methodological bias which can exist in the economic impact analyses (EIA) associated with cultural events. Theoretical considerations were discussed, specifically regarding economic impact as a method of measuring value. Various forms of bias (including data collection, the calculation of visitor numbers, multipliers, defining the area of interest, inclusion of visitor spending, and accounting for benefits only, not costs) are put into a real-life context, through the investigation of economic impact studies conducted on three selected South African festivals (the Volksblad, the Klein Karoo Nasionale Kunstfees, and the National Arts Festival), and one international festival (the Edinburgh Festival). An in-depth comparison of two separate studies conducted at the National Arts Festival (NAF) in 2004 (by Antrobus and Snowball) and 2005 (by Saayman et al.) was made, focussing on the manner in which the economic impact was calculated. Having considered the common forms of bias, and assessing several possible reasons for the difference of approximately twenty million Rand in the advertised economic impacts, it was concluded that, most likely, the miscalculation of visitor numbers was the cause. This was confirmed when the Antrobus and Saayman methods were applied to the 2006 NAF data, and noting that the economic impact figures arrived at were strikingly similar. As such, it is advisable that extreme caution be taken when calculating visitor numbers, as they can significantly influence the outcome of an economic impact study. It is recommended that each study should also have transparent checks in place, regarding the key calculation figures, to ensure that less scrupulous researchers are not as easily able to succumb to the pressure event sponsors might impose to produce inflated impact values.
Keywords: Standard Bank National Arts Festival; Standard Bank National Arts Festival -- Economic aspects; Performing arts festivals- -- Economic aspects -- South Africa; Arts -- Economic aspects -- South Africa; Economic impact analysis; Edinburgh International Festival -- Economic aspects; Klein Karoo Nasionale Kunstefees (Oudtshoorn, -- South Africa) -- Economic aspects; Volksbladfees (Bloemfontein, -- South Africa) -- Economic aspects